The Role of Employing the Robotic Process Automation (RPA) System in Enhancing the Efficiency of the Accountant’s Work and Its Impact on the Quality of Financial Information: An Analytical Study of the Opinions of a Sample of Academics and Professionals in Erbil - Shivan Abdullah Hamad; Mohammed Abdulaziz Mohsin (Zanco Journal of Human Sciences, 2026)
This research aims to study the role of employing the Robotic Process Automation (RPA) system in enhancing the efficiency of accounting work and its impact on the quality of financial information. To achieve the study's objective and test the hypotheses, the researchers developed a questionnaire and distributed it to a sample of respondents specializing in accounting, comprising academics and professionals in the city of Erbil. The statistical software (SPSS) was used for (150) distributed questionnaires to analyze the data and extract the results. The study concluded that employing the Robotic Process Automation system contributes to improving the quality of accounting work as it affects the mediator and dependent variables by (78.40%), and the results of the mediator variable indicate its impact percentage (81.14%). This suggests that the efficiency of accounting work is a pivotal element in linking the use of automation technologies and achieving the quality of financial information. The results of the dependent variable indicate that its impact rate is (81.60%), which suggests that the basic and enhancing characteristics are the main axis in raising the quality of financial information. The study recommended the necessity of economic units adopting the (RPA) technology to enhance their accounting work and raise the quality of their financial information.